Competitive Driving of Autonomous Vehicles - Gabriel Hartmann; Zvi Shiller; Amos Azaria (IEEE Access, 2022)
This paper addresses the issue of autonomous competitive yet safe driving in the context of the Indy Autonomous Challenge (IAC) simulation race. The IAC is the first multi-vehicle autonomous head-to-head competition, reaching speeds of 300 km/h along an oval track modeled after the Indianapolis Motor Speedway (IMS). We present a racing controller that attempts to maximize progress along the track while avoiding collisions with opponent vehicles and obeying the race rules. To this end, the racing controller first computes a race line offline. During the race, it repeatedly computes a small set of dynamically feasible maneuver candidates, each tested for collision with the opponent vehicles. It then selects a collision-free maneuver that maximizes the progress along the track and obeys the race rules. Our controller was tested in a 6-vehicle simulation, managing to run competitively with no collision over 30 laps. In addition, it managed to drive within a close range of the leading vehicle during most of the IAC final simulation race.